2017
DOI: 10.1016/s1470-2045(17)30691-5
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy with or without bevacizumab in patients with resected non-small-cell lung cancer (E1505): an open-label, multicentre, randomised, phase 3 trial

Abstract: SUMMARYBackgroundAdjuvant chemotherapy for resected early stage NSCLC provides modest survival benefit. Bevacizumab, a monoclonal antibody directed against vascular endothelial growth factor, improves outcomes when added to platinum-based chemotherapy in advanced stage non-squamous NSCLC. We conducted a phase III study to evaluate the addition of bevacizumab to adjuvant chemotherapy in early stage resected NSCLC (E1505). The primary endpoint was overall survival.MethodsAdult patients (≥ 18 years old) with ECOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(113 citation statements)
references
References 20 publications
2
108
0
3
Order By: Relevance
“…In the E1505 trial, patients were randomly assigned to receive cisplatin in combination with the investigators' choice of vinorelbin, docetaxel, gemcitabine, or pemetrexed with or without bevacizumab (15 mg/kg). The results of this trial suggested that addition of bevacizumab to chemotherapy does not improve OS or PFS in the adjuvant setting [19]. Notably, these results are similar to adjuvant trials with bevacizumab in other cancers [20,21].…”
Section: Bevacizumab In Early-stage Nsclcsupporting
confidence: 60%
“…In the E1505 trial, patients were randomly assigned to receive cisplatin in combination with the investigators' choice of vinorelbin, docetaxel, gemcitabine, or pemetrexed with or without bevacizumab (15 mg/kg). The results of this trial suggested that addition of bevacizumab to chemotherapy does not improve OS or PFS in the adjuvant setting [19]. Notably, these results are similar to adjuvant trials with bevacizumab in other cancers [20,21].…”
Section: Bevacizumab In Early-stage Nsclcsupporting
confidence: 60%
“…7 Perioperative platinum-based chemotherapy is associated with a survival rate that is only 5.4 percentage points higher than that with surgery alone, with rates of toxic effects of grade 3 or higher of more than 60%. 8,9 PD-1 pathway blockade in patients with early-stage lung cancer may have enhanced antitumor effects owing to greater fitness of host immunity and reduced tumor clonal heterogeneity. 10 Neoadjuvant immunotherapy is attractive, since the primary tumor may be leveraged as an antigen source for expansion and activation of tumor-specific T cells and systemic surveillance of micrometastases.…”
mentioning
confidence: 99%
“…• Consider administering cisplatin/docetaxel to limit time in hospital, as it avoids day 8 administration of gemcitabine or vinorelbine, and has equivalent efficacy. In non-squamous nonsmall cell lung cancer (NSCLC), cisplatin/pemetrexed is an equally efficacious alternative [8]. • In patients with an activating epidermal growth factor receptor (EGFR) mutation, consider a 1-year course of daily oral EGFR tyrosine kinase inhibitor (TKI) as an alternative to adjuvant chemotherapy (currently no phase 3 evidence of superiority available).…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%